Análise de sedimento de fundo: uma amostragem representativa do estuário Potengi/RN - Dantas, Aécia Seleide (2009)
The aim of this study is to quantify the presence of major and minor elements in the sediments of estuary Potengi. Four georeferenced sampling points were used in the study, at which sediment samples were collected in the channel of the river and on the right and left banks. In addition, dissolved oxygen, salinity and water conductivity were taken in situ at the time of sample collection. The percentage of organic matter, determined by gravimetry, and granulometric analysis of the sediment samples were conducted in the laboratory. To quantify the major and minor elements a prior test to open the sample was conducted with standard NIST 1646ª estuarine sediment to choose the best methodology to be adopted. The sediment samples were dissolved in microwaves with nitric acid and chloridric acid, according to methodology proposed by US EPA 3051ª. Quantitative analyses of the elements Al, Fe, Cd, Cr, Cu, Mn, Ni, Pb and Zn were conducted by inductively coupled plasma optical emission spectrometry (ICPOES). The results showed that the partial concentrations of the elements analyzed are below average worldwide shale levels, the standard described by Turekian and Wedepohl (1961)